Evidence for rapid recovery of shark populations within a coral reef marine protected area. (April 2018) - Speed, Conrad W.; Cappo, Mike; Meekan, Mark G.
Abstract: There is limited evidence on the rate at which the shark populations of coral reefs can rebound from over-exploitation, the baselines that might signify when recovery has occurred and the role of no-take Marine Protected Areas (MPA) in aiding this process. We surveyed shark assemblages at Ashmore Reef in Western Australia using baited remote underwater video stations in 2004 prior to enforcement of MPA status and then again in 2016 after eight years of strict enforcement. We found an increase in the relative mean abundance of Carcharhinus amblyrhynchos from 0.16 ± 0.06 individuals h −1 in 2004 to 0.74 ± 0.11 individuals h −1 in 2016, a change that was also accompanied by a shift in the assemblage of sharks to greater proportions of apex species (from 7.1% to 11.9%) and reef sharks (from 28.6% to 57.6%), and a decrease in the proportional abundance of lower trophic level species (from 64.3% to 30.5%). Abundances and trophic assemblage of sharks at Ashmore Reef in 2004 resembled those of the Scott Reefs, where targeted fishing for sharks still occurs, whereas in 2016, abundances and trophic structures had recovered to resemble those of the Rowley Shoals, a reef system that has been a strictly enforced MPA for over 25 years. The shift in abundance and community structure coincident with strict enforcement of the MPA at Ashmore Reef has occurred at a rate greater than predicted by demographic models, implying the action of compensatory processes in recovery. Our study shows that shark communities can recover rapidly after exploitation in a well-managed no-take MPA. Highlights: Sharks were surveyed using baited cameras pre- and post-enforcement of a no-take MPA After eight years of enforcement, abundances of grey reef sharks increased by a factor of 4.6 The proportion of apex species increased from 7.1% to 11.9% of the community The proportion of lower trophic species decreased from 64.3% to 30.5% Grey reef shark abundance increased between 1.6 - 6.6 times faster than predicted by demographic models for this species